Minerals in water: A computational perspective - Raiteri, Paolo; Hyde, A.; Demichelis, Raffaella; Gale, Julian; Stack, A.; Kellermeier, M.; Gebauer, D.; Kerisit, S.; Fenter, P. (AMER CHEMICAL SOC, 2013)
Understanding nucleation and growth of minerals from aqueous solution is an important area both from a fundamental and an industrial point of view and it has always been a challenging area both for experimentalist and theoreticians. In the last decade experimental studies have been increasingly able to provide a more accurate description of mineral water interfaces, yet a full atomistic description is often out of reach. On the other hand computer simulation can play a valuable role in providing an atomistic picture of the interface although a true connection between calculated properties and experimental observables has often been hard to achieve.The constantly increasing power of supercomputers is rapidly closing the gap between size and time scales of simulations and experiments. Furthermore the use of advanced techniques to calculate free energies is making the direct link between experimental and simulated quantities an achievable goal. However, careful calibration and testing of the computational model are of great importance to unsure that the thermodynamic properties of the mineral/water system are correctly reproduced and a reliable picture is obtained from the simulations. Here we illustrate how computer simulation can achieve quantitative agreement with experiments and provide a clear picture of the molecular process in the pre-and post-nucleation stages for systems of mineralogical and of biological importance, such as calcium carbonate, barium sulfate calcium oxalate.